Awareness about loose tobacco ban among tobacco users and vendors : A cross-sectional study - Sinu Ezhumalai (Wolters Kluwer Medknow Publications, 2022)
Background: Ban on smoking in public places reduced the number of smokers considerably. According to Global Adult Tobacco Survey-2, tobacco use is decreased by 3% in Karnataka. However, the loose sale of tobacco products encourages the practice as tobacco users continue to use tobacco by purchasing loose tobacco products. Hence, the present study was carried out to assess the compliance of loose tobacco ban in Bidar city of Karnataka. Aim: The aim of this study is to assess the compliance on loose tobacco ban in Bidar City. Methods: The exploratory research design was used. The study was cross-sectional and community based in nature. Sample Size: 98; 50 vendors and 48 consumers were randomly selected using the time-cluster sampling. Data were collected from 22 different locations using the observation and interview method within 2 km radius of Bidar City. Two separate pretested and predesigned semi-structured interview schedules were administered to tobacco users and vendors. The study was carried out in November 2019. Ethical clearance was obtained from the Institutional Ethics Committee. Statistical analysis was done using the percentages and frequency tables. Results: Majority (96%) of the tobacco users were unaware of loose tobacco ban in Karnataka and prefer to buy cigarettes in loose. Four percent of tobacco users were aware that loose tobacco is banned. Majority of (76%) tobacco users think buying a full pack of cigarettes would increase smoking. There is absolutely no compliance on loose tobacco ban by tobacco vendors.